PENERAPAN METODE BERKISAH DENGAN MENGGUNAKAN BONEKA JARI TERHADAP PERKEMBANGAN BAHASA ANAK USIA 5-6 TAHUN DALAM PERSEPEKTIF HADIS - Nurhidayati, Siti; Lessy, Zulkipli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Language development is one aspect of development in early childhood that is important to develop, because language is a communication tool in conveying messages, desires, opinions to other people and understanding other people's desires, therefore this research aims to determine whether there is language development. is the application of the storytelling method using finger puppets to the language development of children aged 5-6 years in PAUD Ihsan Fikri, Tampan District, Pekanbaru City. This type of research uses quantitative research with teachers and children as subjects. Meanwhile, the object is the application of the storytelling method using finger puppets to the language development of children aged 5-6 years. Data is collected through observation and documentation. Data were analyzed using quantitative descriptive data analysis techniques. These results show that 37% are developing according to expectations (BSH), 32% are developing very well (BSB), 30% are starting to develop (MB) and 0% are not yet developing (BB). Keywords: finger puppets, hadith perspective, language development, storytelling method